Age-related effects on breeding phenology and success of Common Guillemots Uria aalge at a North Sea colony. Issue 3 (2nd July 2016) - Harris, Michael P.; Albon, Steve D.; Wanless, Sarah
ABSTRACT: Capsule: Common Guillemots Uria aalge show delayed breeding and marked age-related changes in reproductive success consistent with improved performance with experience. Aims: To determine age of first breeding and age-related effects on breeding phenology and success of Common Guillemots. Methods: Resighting data from a long-term colour-ringing study of Common Guillemot chicks were combined with observations of breeding phenology and success to follow the recruitment process, breeding phenology and success of 62 birds at a major North Sea colony over a 30-year period. Results: The median age of first breeding of Common Guillemots was 6.6 years. There were no detectable costs of first breeding on return rates or the likelihood of breeding the next season but first time breeders bred later and less successfully. Age of first breeding and lifetime breeding success both varied among individuals but there was no clear optimal age of first breeding and early first breeding was not associated with higher lifetime breeding success. Conclusions: Common Guillemots in the Isle of May population delayed breeding for 3–4 years beyond physiological maturity. The marked increase in breeding success with age was consistent with improved performance with experience rather than selection for higher quality individuals. Findings from this study will inform population models by providing improved estimates of age of first breeding and age-related changes in reproductive performance.